Strategi Peningkatan Kompetensi Dan Produktivitas Kerja Dengan Manajemen Pelatihan Untuk Pengembangan Karyawan - Agrameri, Alvino; Yosepha, Sri Yanthy; Cahaya, Yohanes Ferry (Penerbit Goodwood, 2025)
Purpose: This study examines training management strategies to enhance employee competencies and work productivity in organizations undergoing digital transformation, focusing on identifying critical success factors and developing an integrated framework for effective skill development. Methodology/approach: A systematic literature review was conducted using the Scopus, Web of Science, and Google Scholar databases (2018-2024). Using PRISMA guidelines and NVivo 12 software, 127 empirical studies on training effectiveness and competency development were analyzed via thematic content analysis. Results/findings: Five critical components determine training effectiveness: competency-based needs analysis increased training relevance by 73%; andragogy-based program design improved skill retention by 45-62%; blended learning implementation showed 38% higher engagement and 52% better knowledge application; strong leadership support achieved 67% higher training transfer rates; and comprehensive evaluation systems revealed 23-41% productivity increases within 6-12 months. Conclusions: Effective training management requires the systematic integration of precise needs analysis, evidence-based learning design, optimized delivery methods, and robust evaluation systems. Limitations: This review is Limited to English-language publications and developed countries' contexts, potentially limiting its generalizability to emerging economies and traditional industries with minimal technological integration. Contribution: This study provides an evidence-based integrated training management model for digital transformation contexts, offering practical strategies for HR practitioners and advancing the theoretical understanding of training effectiveness factors for multinational corporations.